Fungal Osteomyelitis of Cuboid Bone Case Report with Literature Review - Pradeep Choudhari; Mohit Mahoviya; Rishabh Chouhan; Aayush K Soni (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Chronic osteomyelitis with sinus formation of right cuboid bone has often been missed, which leads to the morbidity of the patient. Case description: Here, we present a case of a 29-year-old male with fungal involvement of the cuboid bone. Fungal osteomyelitis of cuboid bone is of an unusual occurrence. Delayed diagnosis is one of the prime concerns leading to the progression of the disease and further bone involvement. In our study, we did a prompt diagnosis which changed the progression and treatment of the disease. Conclusion: Early diagnosis and prompt treatment with surgical intervention, antifungal medications, and a multidirectional approach is the key in treating cases of fungal osteomyelitis for immunocompetent and immunocompromised fungal infection.